The Philosophy of «Mangilik El» - seven steps (Journal of Philosophy Culture and Political Science, 2015)
The significance of the article is domestic high educational institutions aim to introduce humanitarian field of social sciences for young learners. Moreover, in order to entrench the notion of «the Mangilik El» in the society's minds, we have to make the system of national world vision concepts more consistent, put in order and enhance its position firmly in the humanitarian knowledge sphere. The notion of «the «Mangilik El» requires new concepts and suggestions in the country's science system. In this respect, a scholar Garifolla Yesim reviews some new ideas in his new program called «The philosophy of «the Perpetual Country» that consists of seven steps». In order to reveal the social meanings of notions like wealth, richness, prosperity, generosity, business skills that are pertaining to Kazakh mindset, a new subject area is to be introduced in our system of knowledge. The overwhelming message of the article is discussion around the stated topic.
Keywords: concept; «Mangilik El» wellness; prosperity; generous; enterprising; continuity; «Jaqsy Qazaq«.